Urban Smartness Vs Urban Competitiveness: A Comparison of Italian Cities Rankings - Papa, Rocco; Gargiulo, Carmela; Franco, Stefano; Russo, Laura (TeMA - Journal of Land Use, Mobility and Environment, 2014)
This paper describes a part of the research carried out by the Department of Civil, Architectural and Environmental Engineering (DICEA) of the University of Naples “Federico II”, within the Project Smart Energy Master for the energy management of territory, financed by PON 04a2_E R&C Axis II, from 2012 to 2015. Today that the idea of smart city draws the attention of urban planners and policy makers and, at the same time, global competitiveness is considered essential for the success of a city, the paper aims to investigate the relationship between the concept of smart city and that of competitive city, identifying common characteristics and differences and answer the question: is “smartness” a new concept for urban studies? The analysis has been conducted in the Italian context, comparing the competitive structure of Italian provinces with their performance as smart cities. To rank Italian provinces because of their level of competitiveness, a previous ranking, carried out in 1995, has been updated with the most recent data available and the new hierarchy, thus obtained, has been compared with that of Italian smartest cities proposed by Forum PA. The benchmarking shows that smartness and competitiveness are strictly connected: today, a city needs to improve its smart quotient in order to be more attractive and so more competitive, in fact, the efficiency and livability of cities, sought by potential citizens, can be improved by using ICTs, as supported by the advocates of smart cities, and represent a strategic factor for gaining a competitive advantage.